The Politics of Class in "The Gift of the Magi" - Kandel, Churamoni (Butwal Campus Journal, 2025)
This paper examines O. Henry’s “The Gift of the Magi” to analyze this story as a politics of class. This narrative story intertwines love with poverty, sacrifice, and class struggle. The narrative begins with Della’s financial hardship, as she saves only one dollar and eighty-seven cents to buy a gift for her husband, Jim. In an act of devotion, she sells her long hair to purchase a chain for Jim’s watch. Simultaneously, Jim sells his watch to buy combs for Della’s hair. These sacrifices portray not only emotional commitment but also the couple’s entrapment within material deprivation and class identity. These exchanged gifts render useless, and only gain symbolic meaning that exceeds their material worth. Drawing on Karl Marx’s notion of commodity fetishism, these gifts reflect objects whose symbolic value obscures the couple’s economic vulnerability. Gift-exchange theory further situates these acts as inalienable gestures that tie love to larger social and cultural frameworks. O. Henry’s use of narrative strategies like irony, coincidence, and sentimental resolution tempers the harshness of poverty while exposing the quiet dignity of resilience. This study employs a qualitative approach, with an interpretive research design to demonstrate the tale’s sentimental appeal and subtle social critique. It expresses broader intersection of class, culture, and human survival.